Mathematical processes and pedagogic practice: Characterization of the teachers in basic and middle education (2020)
This report is generated from a sample of 31 professionals working as math teachers in the basic and middle education levels on six different private institutions located in the urban area of San José de Cúcuta, Colombia. An instrument that takes as reference the five mathematical processes mentioned on the Principles and Standards for the Mathematical Education of the National Council of Teachers of Mathematics – NCTM – 2003, in total 36 items, was applied. Derived from the processing of the recollected data, the poor establishment of connections with other areas of knowledge is identified as the main weakness in the pedagogic practice of the educator. Reflections about the consequences of the impact that it can have on the teaching process appear: Mathematics are shown as an isolated knowledge, disconnected from the educative system and the everyday. It concludes in that, in one way or another, affects the motivation of the student in the learning of mathematics. Actions are proposed to encourage the connections with more areas in the teaching practice.